Estudos de processos térmicos decorrentes da usinagem: aplicação de problemas inversos em furação - Sousa, Priscila Ferreira Barbosa de (2009)
Heat generation is a common problem during any type of cutting, but particularly during a drilling due to the difficulty of conducting heat away from the cutting edge and the fact that the chips remain in contact with the tool for a relatively long time in a hole. Cutting temperatures have strongly influenced both the tool life and the metallurgical state of machined surfaces. Since the direct temperature measurements at the tool-piece interface are very complex this work proposes the estimation of the temperature and the heat flux at the tool-piece interface using the inverse heat conduction problem technique. The aim of the present paper is to develop a three-dimensional inverse algorithm in transient conditions for heat flux and drilling temperature estimation. While various studies modeling the drill are found in the literature, this wok focuses the thermal model of the piece to obtain the interface temperature. This work presents a modified procedure to use the concept of dynamic observers based on Green s functions to solve inverse problems. The modification presented here proposes two different improvements in the original technique: i) A different method of obtaining the transfer function model, GH, using analytical functions instead of numerical procedures, and ii) Definition of a new concept of GH to allow the use of more than one response temperature. Obtaining the heat transfer functions represents an important role in the observer method and is crucial to allow the technique to be directly applied to three-dimensional heat conduction problems with moving heat source. The thermal model is obtained by a numerical solution of the transient three-dimensional heat diffusion equation that considers drill as a heat source moving. To determine the solution equation the finite volume method is used. Several tests using cemented carbide tools drilling a micro allowed steel piece were performed in order to check the model and to estimate the heat flux rate and the temperature at interface tool-piece.